Tindak Pidana Penipuan dalam Perspektif Pasal 386 KUHP dan Hadits Riwayat Ahmad - Hilmi, Muhammad; Arifin, Tajul (Journal of Literature Review, 2025)
This research is motivated by the fact that Article 386 of the Criminal Code states that "Anyone who in a trade transaction intentionally deceives another party to buy or receive goods that are not in accordance with those promised, is threatened with a maximum imprisonment of five years." As one type of property crime, fraud has become a major concern in Indonesian criminal law. Article 386 of the Criminal Code regulates the crime of fraud in trade, especially fraud against the brand, origin, and quality of goods. In the perspective of HR. Ahmad, fraud is not only viewed from the formal perspective of criminal law, but also from the aspects of morality and social justice. The purpose of this study is to study the crime of fraud using a normative analysis of Article 386 of the Criminal Code and a value approach according to HR. Ahmad. This study uses a normative legal study with a conceptual approach and comparative law. The results of the study show that proving the elements of fraud and malicious intent still faces challenges, as well as how important it is to consider the values of justice and honesty as mentioned above.